Analisis Pengaruh Good Corporate Governance Dan Ukuran Komite Audit Terhadap Thin Capitalization Perusahaan Perusahaan Pemilik Modal Asing - Elok Faiqoh Himmah (In Search (Informatic, Science, Entrepreneur, Applied Art, Research, Humanism), 2020)
This study aims to analyze the thin capitalization implemented in companies that have foreign capital. Thin capitalization is a financing structure from internal and external companies. This study uses the independent variable Good Corporate Governance and Committee Size. The population of this study consists of all non-financial companies listed on the Indonesia Stock Exchange from 2017-2019. This study took samples from companies that own foreign capital which are non-financial institutions. This study uses multiple linear regression analysis as a statistical method. The results of this study indicate that the size of the Audit Committee has a significant effect on thin capitalization